2005
DOI: 10.1021/nl0520617
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocating Power Generation in a Chemically Driven Synthetic Muscle

Abstract: A scalable synthetic muscle has been constructed that transducts nanoscale molecular shape changes into macroscopic motion. The working material, which deforms affinely in response to a pH stimulus, is a self-assembled block copolymer comprising nanoscopic hydrophobic domains in a weak polyacid matrix. A device has been assembled where the muscle does work on a cantilever and the force generated has been measured. When coupled to a chemical oscillator this provides a free running chemical motor that generates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
122
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(123 citation statements)
references
References 18 publications
1
122
0
Order By: Relevance
“…Yashin and Balasz have modeled the moving patterns of expansion and contraction set up in these gels [120]. Jones and co-workers have used oscillating pH reactions in the liquid surrounding an acidic block copolymer to drive a gel motor [121,122]. However, their calculations of power density for these gels do give very low values.…”
Section: Gels Driven By Oscillating Reactionsmentioning
confidence: 99%
“…Yashin and Balasz have modeled the moving patterns of expansion and contraction set up in these gels [120]. Jones and co-workers have used oscillating pH reactions in the liquid surrounding an acidic block copolymer to drive a gel motor [121,122]. However, their calculations of power density for these gels do give very low values.…”
Section: Gels Driven By Oscillating Reactionsmentioning
confidence: 99%
“…In vitro experiments using myosin motor proteins and actin gels have demonstrated that motors can modulate stiffness by more than two orders of magnitude (118) (see Figure 13). Although the stimulation of phase transitions has successfully modulated mechanical properties of polymeric materials, the energy conversion efficiency is orders of magnitude lower than the efficiency of individual motor proteins or muscle (31,119,120). High efficiency is thus the key potential advantage of molecular motors over other approaches, even though efficiency is rarely the focus of discussion in either case.…”
Section: Control Of Materials Propertiesmentioning
confidence: 99%
“…When the pH oscillated above and below the apparent pK a of PMAA it caused both a microscopic and macroscopic shape change in the material that was followed by both small angle x-ray scattering (SAXS) and video microscopy, respectively. Later work [61] on the same system focused on the strength of the material during cyclic pH changes. The material was found to have a peak power output of 20 mW kg and striated muscle at 200 W kg −1 [61].…”
Section: Examples Of Actuators Based On the Concept Of Supramolecularmentioning
confidence: 99%
“…Later work [61] on the same system focused on the strength of the material during cyclic pH changes. The material was found to have a peak power output of 20 mW kg and striated muscle at 200 W kg −1 [61]. Following on from this work a similar A-B-A actuator was created with opposite polarity [63,66].…”
Section: Examples Of Actuators Based On the Concept Of Supramolecularmentioning
confidence: 99%